The Apparent Metabolizable Energy and Amino Acid Digestibilities of Copra Meal In Broiler Diets - Burhanudin Sundu (Agricultural Faculty, 2008)
ABSTRACT. The worlds copra meal production amounted to 1.8 million tonnes in 2002 and most of it was produced in Asia. The Philippines and Indonesia contributed approximately 65% of the worlds copra meal production. The main problems of using copra meal in poultry diets are its physical properties along with its nutritional profiles. This study was conducted to determine the physical characteristics and feeding value of copra meal. Physical characteristics were determined by measuring the bulk density and water holding capacity of copra meal and a digestibility study was undertaken to investigate nutrient digestibility, jejunal digesta viscosity and apparent metabolizable energy of copra meal. A total of 28 day old male Ross chicks were given control starter and grower diets from day 1 to 35. From day 36 to 42 , the birds were fed an experimental diet. Faeces were collected for three consecutive days. Jejunal digesta was measured for viscosity and ileal digesta was used for amino acid digestibility measurements.Data indicated that bulk density and water holding capacity of copra meal were poor, being 0.49 g/cm3 and 4.69 g water / g feed respectively. Although the crude proteind and amino acids contents of copra meal were favourable to meet a broiler chickens requirements, their digestibilities were low and lysine digestibility being the lowest while arginine digestibility was high. Dry matter, neutral detergent fibre digestibility and apparent metabolizable energy were also low. The low digestibilities of nutrients were not due to the jejunal digesta viscosity as jejunal digesta viscosity was low.